2018
DOI: 10.1021/acs.nanolett.8b03363
|View full text |Cite
|
Sign up to set email alerts
|

Nanowire Quantum Dots Tuned to Atomic Resonances

Abstract: Quantum dots tuned to atomic resonances represent an emerging field of hybrid quantum systems where the advantages of quantum dots and natural atoms can be combined. Embedding quantum dots in nanowires boosts these systems with a set of powerful possibilities, such as precise positioning of the emitters, excellent photon extraction efficiency and direct electrical contacting of quantum dots. Notably, nanowire structures can be grown on silicon substrates, allowing for a straightforward integration with silicon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 44 publications
4
44
0
4
Order By: Relevance
“…In Fig. 1a, only a few short zincblende insertions, spontaneously formed during the nanowire growth, are visible as darker lines, consistent with our previous observation of a typical density of ~10-30 insertions/µm 13 . The zoom-in in Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In Fig. 1a, only a few short zincblende insertions, spontaneously formed during the nanowire growth, are visible as darker lines, consistent with our previous observation of a typical density of ~10-30 insertions/µm 13 . The zoom-in in Fig.…”
Section: Resultssupporting
confidence: 90%
“…Because of the measured difference in Al content in the core and the shell, we attribute the short-wavelength and long-wavelength branches of the emission to shell and core, respectively. Further details on TEM, EDX and sPL can be found in our previous works 13,17 .…”
Section: Resultsmentioning
confidence: 99%
“…We note that the exciton linewidth did not vary substantially between the three different excitation techniques (FWHM 110 µeV for above bandgap excitation, 104 µeV for TPE, and 108 µeV for RF), while all of them result in a linewidth far from the lifetime limit. This, rather unexpected result, suggests that the limiting factor is intrinsic to the structure and the local environment around the QDs 35 , and not to the excitation process, even if we have shown in our previous work that some QDs show much narrower linewidths, down to 9.4 µeV 18 .…”
Section: Excitation Power Dependenciesmentioning
confidence: 57%
“…In our previous work 18 , we have shown that GaAs QDs can be embedded in AlGaAs nanowires during bottom-up growth in a molecular beam epitaxy reactor, adding new possibilities to the system. For instance, any number of emitters can be precisely positioned within the same nanowire, making the nanowire QDs structure an ideal platform for advanced multi-qubit devices 19,20 that are not possible today with their bulk counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Recent progresses in epitaxial methods, such as vapor-liquid-solid method and selective-area epitaxy, have resulted in the growth of axial heterostructures in nanowires (NWs) regardless of lattice mismatch, i.e., various materials, such as quantum disks and QDs, could be embedded inside host NWs [4][5][6][7][8] . NW axial heterostructures have great potential for future quantum optical applications because flexible band-gap engineering is possible, and the diameter, height, and density of QDs can be controlled by modifying the host NW's geometry.…”
Section: Rational Synthesis Of Atomically Thin Quantum Structures In mentioning
confidence: 99%